Analytical materials on commercial use of some rivers in the Shelikhov Bay in modern conditions - L. L. Khovanskaya; A. I. Barausov (Известия ТИНРО)
Commercial capability of the certain rivers in Shelikhov Bay (Okhotsk Sea) is analyzed for modern conditions. The fishery load on stocks of pacific salmon and char in these rivers is estimated.